Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10745-011-9384-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Benefits of Multi- and Single-Household Grassland Management Patterns in the Qinghai-Tibetan Plateau of China

Abstract: Two grassland management patterns, multihousehold and single-household, have developed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 19 publications
(16 reference statements)
2
55
0
Order By: Relevance
“…As a result, it allows sociocultural systems to complement, rather than fi ght against, biophysical systems. This has not only ecological benefi ts but also signifi cant social ones, particularly for the contintuity of pastoral cultural heritage and indigenous knowledge (Bao et al 2008;Cao et al 2011a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it allows sociocultural systems to complement, rather than fi ght against, biophysical systems. This has not only ecological benefi ts but also signifi cant social ones, particularly for the contintuity of pastoral cultural heritage and indigenous knowledge (Bao et al 2008;Cao et al 2011a).…”
Section: Resultsmentioning
confidence: 99%
“…2 Cao et al (2011aCao et al ( , 2011bCao et al ( , 2013 found ecological benefi ts including greater biomass, species diversity and coverage under multi-household management compared to singlehousehold management in Maqu, with plant species richness increasing with the more extensive areas associated with larger multi-household units.…”
Section: The Policy Of Enclosuresmentioning
confidence: 99%
“…Little can be achieved on the grasslands without the active support and cooperation by the plateau herdsmen. What the herdsmen need is the provision of sound, research-based advice on the implementation, risks and benefits of adopting new practices, and financial aid in the form of low-interest loans or grants, and the willing adoption of techniques and demonstration of the benefits by pioneering herdsmen within their localities (Cao et al 2011). For example, researches, followed by demonstrations of the technology and benefits to be derived from the win-win model for household pasture production, have resulted in its enthusiastic adoption by herdsmen in several areas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent academic studies have observed that group tenure, community cooperatives, and community-based management could be more effective for rangeland management (Banks et al, 2003;Cao et al, 2011;Fernández-Giménez et al, 2012;Zhang and Li, 2009).…”
Section: Rangeland Household Contract Policymentioning
confidence: 99%